2010
DOI: 10.1136/emj.2010.096271
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a successful pre-hospital emergency service in a developing country: experience from Rescue 1122 service in Pakistan

Abstract: As in many other developing countries, emergency medical services, especially pre-hospital emergency care, has long been neglected in Pakistan. Consequently, patients are brought to the emergency departments by relatives or bystanders in private cars, taxis or any other readily available mode of transportation. Ambulances, where they exist, have barely a stretcher and arrangements for oxygen supply. Modern emergency services are considered too costly for many countries. A model of pre-hospital emergency servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 15 publications
0
54
0
Order By: Relevance
“…They used locally available infrastructure for all ambulances and other hardware. The pre-hospital assessment of stroke is not incorporated in this system [25]. …”
Section: Resultsmentioning
confidence: 99%
“…They used locally available infrastructure for all ambulances and other hardware. The pre-hospital assessment of stroke is not incorporated in this system [25]. …”
Section: Resultsmentioning
confidence: 99%
“…These initiatives have involved formal and informal EMS systems, including research on ambulance systems and the provision of first aid courses to first responders. For example, a descriptive study from Pakistan showed neglect of EMS systems (82), and a prospective study from Nigeria showed that most RTI patients are brought to the hospital by relatives (71). Other prehospital studies in LMICs have investigated the training of EMS providers (7,47) and the community knowledge of available EMS services (6).…”
Section: Interventions For Unintentional Injuriesmentioning
confidence: 99%
“…Rescue 1122 is an emergency service that offers ambulance, fire, emergency response teams, water rescue and safer community programme to over 80 million people in the Punjab [20,21]. The Punjab is the largest province of Pakistan, with 36 districts.…”
Section: Study Settingmentioning
confidence: 99%
“…The service operates in urban settings and works through a toll-free number 1122. It is state funded and operates over 24 hours, 7 days a week [20,21].…”
Section: Study Settingmentioning
confidence: 99%